The role of artificial intelligence in enhancing biology education: A bibliometric perspective - Arinda Eka Lidiastuti; Rikardus Herak; Handi Darmawan; Netti Yuniarti; Stephani Yane (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2025)
Mapping of research trends, collaborations, and developments in the application of artificial intelligence (AI) in biology education is still inadequate and has not been systematically explored. Evidence-based insight investigations that can guide future research and provide guidance on effective AI integration strategies in biology education are needed. Biology learning, which involves abstract concepts and complex data, is expected to be integrated with AI to support the innovation of interactive learning tools, improve critical thinking skills, and enrich the learning experience. This research aims to analyze the role of AI in improving the quality of biology education through a bibliometric approach. This research uses data from Scopus with the keywords “artificial AND intelligence AND biology AND education,” which includes 302 publications from 2000 to 2025. The analysis was conducted using Bibliometrix and Biblioshiny on the RStudioVR platform. The results show a significant upward trend in publications, especially after 2018, with a peak in 2023. The United States and China are the main contributors to these publications, with scientific articles (40.9%) and conference papers (25.1%) as the most dominant document types. In addition, Lecture Notes in Computer Science emerged as the most relevant source, demonstrating the important role of computer science in the development of AI for biology education. The findings are expected to provide strategic insights for more effective AI implementation in the future.Abstrak. Pemetaan mengenai tren penelitian, kolaborasi, dan perkembangan dalam penerapan kecerdasan buatan (AI) di bidang pendidikan biologi masih belum memadai dan belum dieksplorasi secara sistematis. Penyelidikan wawasan berbasis bukti yang dapat mengarahkan penelitian masa depan dan memberikan panduan strategi integrasi AI yang efektif dalam pendidikan biologi diperlukan. Pembelajaran biologi yang melibatkan konsep-konsep abstrak dan data kompleks diharapkan dapat diintegrasikan dengan AI untuk mendukung inovasi alat bantu pembelajaran yang interaktif, meningkatkan kemampuan berpikir kritis, dan memperkaya pengalaman belajar. Penelitian ini bertujuan untuk menganalisis peran AI dalam meningkatkan kualitas pendidikan biologi melalui pendekatan bibliometrik. Penelitian ini menggunakan data dari Scopus dengan kata kunci “artificial AND intelligence AND biology AND education” yang mencakup 302 publikasi dari tahun 2000 hingga 2025. Analisis dilakukan menggunakan Bibliometrix dan Biblioshiny pada platform RStudioVR. Hasil penelitian menunjukkan adanya tren peningkatan signifikan dalam publikasi, terutama setelah 2018, dengan puncak pada 2023. Amerika Serikat dan China menjadi kontributor utama dalam publikasi ini, dengan artikel ilmiah (40,9%) dan makalah konferensi (25,1%) sebagai jenis dokumen yang paling dominan. Selain itu, Lecture Notes in Computer Science muncul sebagai sumber paling relevan, menunjukkan peran penting ilmu komputer dalam pengembangan AI untuk pendidikan biologi. Temuan ini diharapkan dapat memberikan wawasan strategis untuk implementasi AI yang lebih efektif di masa depan.